Optimum integration procedures for supercontinuum simulation - Rieznik, Andrés Anibal (2012)
We study numerical solutions of the generalized nonlinear Schro¨ dinger equation (GNLSE), focusing on the advantage of integrating the nonlinear part of the equation in the frequency domain (FD), rather than in the time domain (TD), when simulating supercontinuum generation in optical fibers. We show that integration of the nonlinear operator in the FD is more efficient than its integration in the TD. We analyze different adaptive stepsize algorithms in combination with the interaction picture integration method and show that their performance strongly depends on whether integration of the nonlinear operator is performed in the FD or TD. We find that the most efficient procedure for supercontinuum simulation in optical fibers results from solving the nonlinearity in the FD and applying the recently introduced conservation quantity error adaptive step-size algorithm.